The influence of food industry advertising on children's eating habits: a literature review (Research, Society and Development, 2021)
This study discusses the influence of advertising in the food industry on children's eating habits. The technological advance experienced by today's society brings unprecedented changes in the standard of living, so it is necessary to be aware of the use of these technologies in childhood. In this sense, advertising campaigns involving food are increasingly part of the child's world, influenced by their eating habits. The study aims to discuss the influence of advertising on food choices aimed at children. For this, an integrative bibliographic review of descriptive character with a qualitative approach was carried out. As a data source, electronic journals and books with a time cut from 2015 to 2021 that address the proposed theme were used. It showed that advertising in digital media does not have supervision in which Brazilian regulations ensure and that children have little monitoring by their families in accessing the network, making them susceptible to the influence of campaigns that address unhealthy eating. At the expense of an inadequate diet without nutrients and a long time spent in front of the screen, these children gain fat and can reach childhood obesity, which is a public health problem today. As it is a phase of physical and cognitive development, it is essential that the child has a healthy eating habit and that they do physical activities, therefore, ball games, running, climbing, among others, are essential to maintain the child's health and quality of life.